Dos testimonis més del Breuiarium apostolorum - Alturo i Perucho, Jesús (Miscel·lània litúrgica catalana, 2016)
Identification of two new manuscripts witnesses to the Breuiarium apostolorum: one dates from the end of the ninth century and probably originated in Septimania, and the other around the year 1180 and possibly copied by some ecclesiastical center of Meaux region, although it is coming from the monastery of Santa Maria de Ripoll or from Sant Salvador de Breda.